Evidence that Clostridium difficile TcdC Is a Membrane-Associated Protein - Govind, Revathi (American Society for Microbiology, 2006)
Clostridium difficile produces two toxins, A and B, which act together to cause pseudomembraneous colitis. The genes encoding these toxins, tcdA and tcdB, are part of the pathogenicity locus, which also includes tcdC, a putative negative regulator of the toxin genes. In this study, we demonstrate that TcdC is a membrane-associated protein in C. difficile.